Patent watch [electronics and communications devices]. - Savage, P.R.
This paper describes three new patented devices. First is a two-part device, patented by the US Navy, that uses a detector and a jammer to protect aircraft from attack by infrared homing missiles. Second, is a smart cooling system that features a fan and two thermal sensors to keep laptop from overheating. One sensor measures the temperature of incoming air, while the other measures the temperature of air after it passed over the microprocessor. Last, is RAID, a system for smarter and safer storage of information.
Keywords: RAID; US Navy; Aircraft protection; Information storage; Infrared homing missiles; Jammer; Laptop; Microprocessor; Overheating; Patent; Smarter cooling system; Temperature measurement; Thermal sensors